2021
DOI: 10.1021/acsomega.1c01296
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth Molybdate Nanoplates Supported on Reduced Graphene Oxide: An Effective Nanocomposite for the Removal of Naphthalene via Adsorption–Photodegradation

Abstract: Polycyclic aromatic hydrocarbons are a class of persistent organic water pollutants that raise serious concerns owing to their carcinogenicity and other negative impacts on humans and ecosystems. In this study, Bi 2 MoO 6 /reduced graphene oxide (rGO) nanocomposites were designed and prepared for the adsorption-assisted photodegradation of naphthalene molecules in an aqueous medium. The synthesized Bi 2 MoO 6 nanoplates and Bi 2 MoO 6 /rGO nanocomposites were characterized by X-ray diffraction, Fourier transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 49 publications
(73 reference statements)
1
19
0
Order By: Relevance
“…7(b), which are attributed to Bi 4f 7/2 and Bi 4f 5/2 , respectively. 45,46 In agreement with the other two, the peaks for Bi 2 Mo 3 O 12 are shifted to 165 eV, signifying the trivalent oxidation state for bismuth (Bi 3+ ). The Mo 3d spectrum in Fig.…”
Section: Resultssupporting
confidence: 71%
“…7(b), which are attributed to Bi 4f 7/2 and Bi 4f 5/2 , respectively. 45,46 In agreement with the other two, the peaks for Bi 2 Mo 3 O 12 are shifted to 165 eV, signifying the trivalent oxidation state for bismuth (Bi 3+ ). The Mo 3d spectrum in Fig.…”
Section: Resultssupporting
confidence: 71%
“…[1][2][3][4] So far, photocatalysis and adsorption degradation are two of the most favorable and environmentally friendly strategies for eradicating organic dyes in wastewater. 5 Previous studies revealed the amazing construction of a novel photocatalysis system on account of its efficiency, robustness, less expensive and recyclable properties. 6 As one of the most ideal strategies, enhanced visible light harvesting photocatalysis has been extensively reported in the removal of organic dyes and damaging constituents in wastewater owing to its clean and energy-conservation particularities.…”
Section: Introductionmentioning
confidence: 99%
“…38 The C 1s peak of GM-Bi 1.9 Gd 0.1 Mo 2 O 9 was much stronger than that of GM-Bi 1.9 Ce 0.1 Mo 2 O 9 centered around 285.3 eV and was due to the CO bond, confirming the residence of residual carbon in the as-synthesized rGO-modified self-assembly. 39…”
Section: Resultsmentioning
confidence: 99%